Communicating design knowledge to support technology management in the manufacturing industry:: an application of pragmatic constructivism - Mämmelä, Janne; Korhonen, Tuomas; Juuti, Tero; Julkunen, Pasi (Proceedings of Pragmatic Constructivism, 2019)
The aim of this paper is to the advance pragmatic constructivist understanding about communication in the product development context. In particular, the paper provides new understanding about how proactive truth about design knowledge can be constructed and communicated within product development actors. The paper shows how company representatives in the manufacturing environment, e.g., managers and engineers can together understand the customervalue- creation mechanisms of a specific product and integrate their expert knowledge into visual form. Building the collective understanding requires communication between these actors. Ultimately, the actors may be able to construct a useful proactive truth about related business potentials and thereby support technology management in the product development context.